2020
DOI: 10.1016/j.jgar.2020.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxychloroquine use in hospitalised patients with COVID-19: An observational matched cohort study

Abstract: Highlights In this observational study, no clear clinical benefit associated with HCQ use in COVID-19 patients was found. In our centre, HCQ use did not decrease the risk of in-hospital death. HCQ use did not decrease the time to clinical improvement or the length of hospitalisation. Antimicrobial stewardship programmes can allow for the safe evaluation of agents and treatments against COVID-19.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 5 publications
3
12
0
Order By: Relevance
“…Hence, patients who received HCQ would be expected to require a longer stay. Indeed, when these factors were adjusted for in the analysis, the difference was non-significant, which is consistent with other reported data (41). These findings were also reported in a randomized clinical trial conducted in china on 150 COVID19 patients.…”
Section: Discussionsupporting
confidence: 91%
“…Hence, patients who received HCQ would be expected to require a longer stay. Indeed, when these factors were adjusted for in the analysis, the difference was non-significant, which is consistent with other reported data (41). These findings were also reported in a randomized clinical trial conducted in china on 150 COVID19 patients.…”
Section: Discussionsupporting
confidence: 91%
“…Hence, patients who received HCQ would be expected to require a longer stay. Indeed, when these factors were adjusted for in the analysis, the difference was non-significant, which is consistent with other reported data [ 43 ]. These findings were also reported in a randomized clinical trial conducted in China on 150 patients with COVID-19.…”
Section: Discussionsupporting
confidence: 91%
“…Observational studies have shown that HCQ monotherapy or HCQ + AZM combination therapy might reduce mortality due to COVID-19 or promote clinical improvement [ 43 55 56 57 58 ] and that co-administration of HCQ and steroids could reduce the risk of hospitalization by 50–60% among those who were in the early stages of COVID-19 and not yet been hospitalized [ 59 ]. However, other studies have shown that these treatments did not reduce the mortality rate and worsened arrhythmia [ 32 40 41 42 60 61 62 63 64 65 ]. Some studies have shown that HCQ [ 34 ] and combination therapy with HCQ + AZM could help reduce the time to viral negativity [ 36 38 ].…”
Section: Resultsmentioning
confidence: 99%